K'mohung promoting awareness about K'mohung through a video documentary - Tupas, Karel Jean M.; Perez, Teody Boylie R. (2018)
Documentary as a visual art can be an effective tool to promote awareness to the public about an issue. Hence, this is the reason the researcher has chosen this tool in order to promote awareness and disseminate information about K?mohung to the community of Lake Sebu. This production thesis answer the design problem: ?Producing a video documentary that will inform and promote awareness about K?muhong specifically to the people of Lake Sebu?. The problem about the lack of awareness and information about K?mohung in Lake Sebu has been realized through the theory of Cognitive Dissonance by Leon Festinger. This theory has been incorporated in this study, hence a new framework was created and became the primary component in the production process: Pre-production (data gathering phase, determining the questions to ask and shot list), Production (shooting the interviews and fillers) and the Post-production (scriptwriting, recording and editing). Perspectives of the local people and the knowledge of experts on K?mohung can be seen in this documentary. The gravity of the disaster was emphasized in the video with the help of fillers. The proponent of this study envisions that his documentary will be shown to the local people of Lake Sebu through their local government unit. This could help increase awareness and understanding on the issue on K?mohung.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2018